2009
DOI: 10.1002/art.25005
|View full text |Cite
|
Sign up to set email alerts
|

HLA–DR alleles determine responsiveness to Borrelia burgdorferi antigens in a mouse model of self‐perpetuating arthritis

Abstract: Objective. Arthritis is a prominent manifestation of Lyme disease, which is caused by infection withConclusion. This study provides direct evidence that in the presence of HLA-DR11, the immune response against Bb antigens is directed toward a protective antibody response. In contrast, an inflammatory Th1 response is induced in the presence of DR4. These observations offer an explanation for the differential genetic susceptibility of DR4؉ and DR11؉ individuals to the development of chronic Lyme arthritis and, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 42 publications
0
16
0
1
Order By: Relevance
“…While the MB, MR, and ONLP STs diverged from U.S. STs and those from QCTH, they were most closely related to, and often had likely ancestors in, STs found immediately to the south: MB with the MW STs and MR with the NE STs. However, STs from ONLP, which lies on longitude 80°W, which nowadays separates NE and MW populations (14), had elements of relation and ancestry to both MW and NE STs. Inferred founders with Ͼ60% bootstrap support were STs from the northeastern United States for two clonal complexes; other inferred founder (or possible founder) STs had Ͻ60% bootstrap support, and these also included the NE STs, the MW STs, and both the NE and MW STs (Fig.…”
Section: Nucleotide Sequence Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…While the MB, MR, and ONLP STs diverged from U.S. STs and those from QCTH, they were most closely related to, and often had likely ancestors in, STs found immediately to the south: MB with the MW STs and MR with the NE STs. However, STs from ONLP, which lies on longitude 80°W, which nowadays separates NE and MW populations (14), had elements of relation and ancestry to both MW and NE STs. Inferred founders with Ͼ60% bootstrap support were STs from the northeastern United States for two clonal complexes; other inferred founder (or possible founder) STs had Ͻ60% bootstrap support, and these also included the NE STs, the MW STs, and both the NE and MW STs (Fig.…”
Section: Nucleotide Sequence Analysismentioning
confidence: 99%
“…The 564 B. burgdorferi samples used for analyses in this study were divided into 111 STs. Of the STs already in the mlst.net database, 18 STs were unique to California, 27 STs were unique to the Midwest (6 of which have been found in "midwestern" Canada [14]), 29 STs were unique to but widespread in the Northeast (including 14 found in eastern Canada, from eastern Ontario to the Maritimes [14]), and 6 STs occurred in both the Midwest and the Northeast (Table 2 and Fig. 1).…”
Section: Nucleotide Sequence Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are more significant as it has been shown that the HLA type does not confer risk for infection with B. burgdorferi overall but merely to the outcome. More recently a DR4-positive mouse model has been established (Iliopoulou et al, 2008;Iliopoulou et al, 2009). The HLA associations have not been confirmed in European patients, perhaps also because of the greater species diversity there.…”
Section: Molecular Mimicry and Induction Of Autoimmunitymentioning
confidence: 99%
“…The ability to identify which strains cause disseminated LD, and to be able to predict their occurrence in Canada by understanding any associations with environmental factors or animal hosts, would permit implementation of preventive public health actions that are "smarter" by targeting the greatest effort at protecting the populations at the greatest risk from severe LD. We also need to identify pathogenic strains for future studies that can elucidate the interactions of the human, animal, and bacterial genomes that result in infection and disease (28,29,30,31).…”
mentioning
confidence: 99%